The maintenance and spread of cooperation in social networks in natural populations - Gokcekus, S (2023)
Social interaction is crucial for social animals to thrive, but it comes with both benefits and costs. The social network approach helps to identify how social processes like cooperation are influenced by individual and population-level characteristics. Factors like individual recognition, familiarity, and social stability play a role in promoting tolerance and cooperation; and understanding these factors can provide insights into how social networks, cooperation, and other social behaviors evolve in different species. In this thesis, I examine how social processes interact with spatial and temporal factors to influence fitness and other outcomes in wild birds (Paridae).